Analysis of gene polymorphisms TGF? rs 1058213 to cleft lip cases with or without a non-syndrome cleft palate in Riau Malay Ethnic - Masrial Masrial; Yanwirasti Yanwirasti; Sumaryati Syukur; Endang Syamsudin (Journal of Dentomaxillofacial Science, 2018)
Objective: This study aims to determine the role of gene polymorphism TGFÎ± rs 1058213 in cases of cleft lip with or without cleft palate nonsyndrome in the Riau Malay tribe.Material and Methods: DNA extraction of venous blood and polymorphism TGFÎ± rs 1058213 was assessed using the Restriction Fragment Length Polymorphism-PCR (RFLP-PCR) working method and followed by sequencing. Genotyping SNP rs1058213 in the TGFÎ± gene was performed by the RFLP-PCR method in control and CLP NS patients. The data was assessed using the test statistic premises T-testÂ difference test.Results: The total sample size included 68 samples consisting of 34 CLP NS samples and 34 control samples. The cases of CLP NS occurred more in men than women, 20 cases (59%) and 14 cases (14%), respectively.Conclusion: There was no significant difference between TGFÎ± rs 1058213 gene polymorphisms in CLP NS and controls in the Riau Malay tribe.